Massacre at Camp Grant : forgetting and remembering Apache history - Colwell, Chip (John Stephen), 1975- (University of Arizona Press, 2007)
"On April 30, 1871, an unlikely group of Anglo-Americans, Mexican Americans, and Tohono O'odham Indians massacred more than a hundred Apache men, women, and children who had surrendered to the U.S. Army at Camp Grant, near Tucson, Arizona. Thirty or more Apache children were stolen and either kept in Tucson homes or sold into slavery in Mexico. Planned and perpetrated by some of the most prominent men in Arizona's territorial era, this organized slaughter has become a kind of "phantom history" lurking beneath the Southwest s official history, strangely present and absent at the same time. Seeking to uncover the mislaid past, this book begins by listening to those voices in the historical record that have long been silenced and disregarded." "Massacre at Camp Grant fashions a multivocal narrative, interweaving the documentary record, Apache narratives, historical texts, and ethnographic research to provide new insights into the atrocity. Thus drawing from a range of sources, it demonstrates the ways in which painful histories continue to live on in the collective memories of the communities in which they occurred. Chip Colwell-Chanthaphonh begins with the premise that every account of the past is suffused with cultural, historical, and political characteristics. By paying attention to all of these aspects of a contested event, he provides a nuanced interpretation of the cultural forces behind the massacre, illuminates how history becomes an instrument of politics, and contemplates why we must study events we might prefer to forget."--Jacket